Il processo di formazione delle strategie aziendali nelle medie imprese: un’analisi per casi - Penco, Lara (Piccola Impresa / Small Business, 2011)
The aim of this work is to study the strategy formation process in the medium sized firms, focusing attention on their specificities respect to small and big firms. The paper describes the findings that have emerged from a investigation focused on a selected cases of firms belonging to the Ligurian region and operating in the food industry. The paper is articulated in three sections. The first section defines the tipology “medium sized firms”. The second presents theoretical framework. The literature review helps to individuate the fundamentals and tools necessary to analyse the strategy formation process in the mediumsized firms. The third describes the methodology and shows the principal results of the case study research. The last section is focused on the concluding remarks.